Pengaruh Bioconc Expired Dalam Kuat Tekan Beton - Arifien Nursandah; Faizah Rizki Jannah (AGREGAT, 2017)
The method used in this research is the method of the Department of Environment (DOE) which is usually referred to the design of the English manner stipulated in SNI 03-2834-2000 namely "Procedure for Making Plans Mixed Concrete Normal". Making concrete mix Bioconc in this study as many as 36 pieces with aged care 7, 14, 21 and 28 days and testing materials in the form slinder 30 x 15 cm with a variation of normal concrete without mix and concrete with the addition of additives Bioconc ie 20% and 30% of the sheer number of cement. Quality of the concrete is planned fc '30 MPa. The results of the study with normal concrete compressive strength of the resulting 24.94 MPa, using additives Bioconc 20% of the compressive strength of the resulting 24.63 MPa, using a 30% Bioconc compressive strength of 19.94 MPa produced using additives as an additive in mixed concrete gives concrete strength decreased from normal concrete mix. It is advisable to pay attention to several factors such as the mix design especially for the concrete mix additives, Cement Water Factor (FAS), material testing, concrete casting and solidification.